Effects of photoperiodism of the chlorophyll content and leaf ultrastructure in the winged bean Psophocarpus tetragonolobus(L.) DC. - Tabbada, Reynaldo A.; Flores, Ma. Agnes A. (1984)
The effects of varying photoperiods on the chlorophyll content and chloroplast ultrastructure in the winged bean were investigated. Longer photoperiods increased chlorophyll content with accompanying alterations in chloroplast ultrastructure